Evaluation of Sample Preparation Protocols for the 14C Dating of Tupiguarani Pottery in Southeastern Brazil. Issue 3 (19th August 2016) - Oliveira, Fabiana M; Macario, Kita D; Pereira, Bruna B; Buarque, Angela; Chivall, David; Alves, Eduardo Q; Ramsey, Christopher Bronk
Abstract: This study evaluates the radiocarbon dating of ceramic samples from Tupiguarani sites in Brazil, a settlement type dating up to 3000 cal BP. In this work, residues from ceramic samples from four archaeological sites in Rio de Janeiro (Morro Grande, Serrano, Barba Couto, and Bananeiras) were analyzed. In order to identify the most suitable sample preparation protocols, the humic fraction was isolated from the bulk material at the Oxford Radiocarbon Accelerator Unit (ORAU), whereas the acid-base-acid (ABA) residue fraction method was applied at the Radiocarbon Laboratory of the Fluminense Federal University (LAC-UFF). The dating results were compared to the current knowledge about the occupational periods of the sites. For the Morro Grande site, the results of humic and ABA residue fractions show a difference of more than 1500 yr. For the Serrano site, the 14 C ages obtained from the two pretreatments are identical, and as with the Barba Couto and Bananeiras sites, indicate an occupation during the Brazilian colonial period of the 16th century AD and are compatible with the archaeological data.